Perhitungan Harga Pokok Produksi Serta Harga Pokok Penjualan Terhadap Laba Penjualan: Studi Kasus pada UMKM Cilok Wonogiri - Ernawati, Ernawati; Sihabudin; Robby Fauji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of production costs and cost of goods sold on profits generated by MSMEs in Cilok Wonogiri. The elements that form production costs are production costs, including: raw material costs, direct and indirect labor costs, general production costs and inventory of goods in process, including: inventory of goods in process and inventory of goods. ongoing. Meanwhile, the cost of goods sold factor includes total production costs and finished product inventory (initial finished product inventory and final finished product inventory). These factors will influence the selling price of the product. Primary and secondary data are the types of data used in research. Primary data was taken from direct observation of subjects to obtain accurate data along with the results of company interviews. Secondary data was collected through company records regarding data relating to production costs and cost of goods sold which will affect the profits obtained from sales of Wonogiri cilok. Researchers examine production costs using company calculations and production cost data for 2022. The analysis technique used by the author is a quantitative descriptive analysis method. Quantitative descriptive analysis is used to explain the calculation of production costs according to the full cost method, then this information is used as a basis for determining product selling prices to determine MSME profits.